The Effect of the Problem-Based Learning Model Using the AMK (Mystery Case Envelope) Media on Third-Grade Students’ Critical Thinking Skills in Civic Education at MI Mathlaul Anwar - Indah Permata Sari; Khaidir Fadil Fadil; Ade Irma Imamah (Jurnal Evaluasi dan Pembelajaran, 2026)
This study aims to determine the effect of the Problem-Based Learning (PBL) model, supported by the AMK (Mystery Case Envelope) medium, on the critical thinking skills of third-grade students in the Civic Education subject at MI Mathlaul Anwar. The research method used was a quantitative approach with an experimental design. The sample consisted of 60 students divided into an experimental class (30 students) and a control class (30 students). The data analysis technique used was an essay test that had been tested for validity and reliability. The results showed that the average posttest score of the experimental class (83.80) was higher than that of the control class (75.73). The independent sample t-test yielded a significance value of 0.000 < 0.05, indicating a significant effect of the PBL model supported by the AMK media on students’ critical thinking skills